An infectious cDNA clone of a growth attenuated Korean isolate of MERS coronavirus KNIH002 in clade B. Issue 1 (1st January 2020) - Kim, Minwoo; Cho, Hee; Lee, Seung-Hoon; Park, Woo-Jung; Kim, Jeong-Min; Moon, Jae-Su; Kim, Geon-Woo; Lee, Wooseong; Jung, Hae-Gwang; Yang, Jeong-Sun; Choi, Jang-Hoon; Lee, Joo-Yeon; et al.
ABSTRACT: The MERS-CoV isolated during the 2015 nosocomial outbreak in Korea showed distinctive differences in mortality and transmission patterns compared to the prototype MERS-CoV EMC strain belonging to clade A. We established a BAC-based reverse genetics system for a Korean isolate of MERS-CoV KNIH002 in the clade B phylogenetically far from the EMC strain, and generated a recombinant MERS-CoV expressing red fluorescent protein. The virus rescued from the infectious clone and KNIH002 strain displayed growth attenuation compared to the EMC strain. Consecutive passages of the rescued virus rapidly generated various ORF5 variants, highlighting its genetic instability and calling for caution in the use of repeatedly passaged virus in pathogenesis studies and for evaluation of control measures against MERS-CoV. The infectious clone for the KNIH002 in contemporary epidemic clade B would be useful for better understanding of a functional link between molecular evolution and pathophysiology of MERS-CoV by comparative studies with EMC strain.